Atmospheric stability index during tropical cyclone seroja in Nusa Tenggara - Febby Debora Abigael; Muhammad Fany Nur Wibowo; Yosafat Donni Haryanto (LPPMPK- Universitas Muhammadiyah Cileungsi, 2026)
Tropical cyclones are low-pressure systems with strong wind circulation formed in tropical waters. Tropical Cyclone Seroja (category 2) struck Nusa Tenggara on April 5, 2021, causing more than 150 casualties. This study aims to analyze the dynamics of atmospheric stability indices (K-Index/KI, Total-Totals Index/TTI, and Convective Available Potential Energy/CAPE) during four cyclone phases: pre-formation (April 2), maximum intensification (April 5), early dissipation (April 10), and final phase (April 12, 2021), and compare them with DJF 2017–2021 climatological conditions to identify atmospheric anomalies. ERA-5 reanalysis data with 0.25° × 0.25° resolution were spatially visualized using Python. Results show that KI significantly increased from moderate category (30–32) during the DJF period to strong category (38) during formation and intensification phases (April 2–5), then decreased to weak-moderate (26–35) during dissipation (April 10–12). TTI showed minimal fluctuations (38–44), relatively consistent with the DJF period (39–43). CAPE increased from weak category (500–1000 J/kg) during the DJF period to moderate category with values reaching 1750–2500 J/kg at the cyclone peak (April 5), then weakened during dissipation. It can be concluded that KI and CAPE are responsive indicators of changes in atmospheric instability during Tropical Cyclone Seroja, especially during formation and intensification phases, while TTI tended to be stable compared to climatological conditions